2020
DOI: 10.1177/0363546520902475
|View full text |Cite
|
Sign up to set email alerts
|

Early Radiographic Healing and Functional Results After Autologous Osteochondral Grafting for Osteochondritis Dissecans of the Capitellum: Introduction of a New Magnetic Resonance Imaging–Based Scoring System

Abstract: Background: Autologous osteochondral grafting (OG) is an option in the treatment of capitellar osteochondritis dissecans (COCD). However, radiographic healing after this procedure has not been well documented. Purpose: To develop a magnetic resonance imaging (MRI)–based scoring system specific for evaluating healing after single-plug OG in COCD and to evaluate correlation between radiographic healing and early clinical outcomes. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…31 Recently, Sayani et al 32 described a four-stage grading system that is based on unified existing validated classification systems and can be used to classify the severity of the condition and to guide treatment decisions. Wang et al 33 have introduced an MRI-based scoring system designed for postoperative evaluation of the healing after single-plug osteochondral autograft transplantation (OAT). No single classification is universally accepted or used to guide treatment decisions or predict prognosis in OCD.…”
Section: Radiology and Classificationmentioning
confidence: 99%
“…31 Recently, Sayani et al 32 described a four-stage grading system that is based on unified existing validated classification systems and can be used to classify the severity of the condition and to guide treatment decisions. Wang et al 33 have introduced an MRI-based scoring system designed for postoperative evaluation of the healing after single-plug osteochondral autograft transplantation (OAT). No single classification is universally accepted or used to guide treatment decisions or predict prognosis in OCD.…”
Section: Radiology and Classificationmentioning
confidence: 99%
“…28 New research has shown that MRI-based quantitative evaluation tools appear to correlate with early clinical function and may be useful in guiding activity progression. 29…”
Section: Authors' Preferred Surgical Techniquementioning
confidence: 99%